Pengaruh Budaya Organisasi, Kecerdasan Intelektual (Iq) dan Kecerdasan Emosional (Eq) Terhadap Prestasi Kerja Karyawan PT Cipta Ternak Sehat Indonesia - Rahma, Anila; Syahputra, Erwin (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
This research aims to empirically test the influence of organizational culture, intellectual intelligence and emotional intelligence on the work performance of PT employees. Create Indonesian Healthy Livestock by researchers. This research uses independent variables, namely organizational culture, intellectual intelligence and emotional intelligence as well as the dependent variable, namely employee work performance. The sample in this research were all employees of PT Cipta Ternak Sehat Indonesia who worked in the office. Data obtained through observation, interviews. The sampling technique in this research was carried out using a non-probability sampling method, namely saturated sampling. The analysis technique uses multiple linear regression analysis with hypothesis testing t test and F test. The results of this research show that organizational culture, intellectual intelligence and emotional intelligence have a partial and simultaneous influence on work performance. This is known from the results of the organizational culture t test with a sig t value of 0.000<0.05, the intellectual intelligence t test with a sig t value of 0.000<0.05, the emotional intelligence t test with a sig t value of 0.000<0.05, and the F test with a sig value of F 0.000<0.05.